When Lisbon met the Team 10 Cluster City - João Cunha Borges; Teresa Marat-Mendes (Joelho)
In the aftermath of the Doorn Manifesto (1954), Team 10 members synthesize their earlier projects into a new urban model: the Cluster City. In 1961, the Lisbon Technical Office for Housing (Gabinete Técnico de Habitação) – GTH was established to support the Portuguese government in solving an ongoing housing shortage. Soon, this new office planned the urbanization of the Chelas Valley, a large suburban agricultural area situated in the East area of Lisbon. This plan tested approaches to neighbourhood planning unprecedented in the municipality. The Zone I of the Plan, by Francisco Silva Dias and Luís Vassalo Rosa (1966) was the first to be implemented, echoing in practice the principles of the Doorn Manifesto.